Istikhda>m Lu’bah al Hamsi at-Tasalsul Litanmiyati Hifzi al Mufrada>t Lada> Ta>liba>t al Fasl at Ta>si’ fi> al Madrasah as S|a>nawiyah “ al Munawwarah” Jombang. - Masbellia Ningrum; Abdul Qodir (Program Studi Pendidikan Bahasa Arab, 2024)
Ninth-grade students of Madrasah Tsanawiyah Al-Munawaroh Jombang said they did not feel lazy and sleepy when learning Arabic, especially mufrhodat using a chain whisper game. Therefore, researchers are interested in researching the use of chain whisper games to develop memorization of mufrhodat of ninth-grade students of Madrasah Tsanawiyah Al-Munawaroh Jombang. This study aims to: 1) determine the process of using chain whisper games to develop memorization of mufrhodat in ninth-grade students of Madrasah Tsanawiyah Al-Munawaroh Jombang. 2) knowing the positive and negative impacts of the use of serial whisper games to develop memorization of mufrhodat in ninth-grade students of Madrasah Tsanawiyah Al-Munawaroh Jombang. This research uses qualitative methods with a descriptive approach, and data collection techniques in the form of observation, interviews, and documentation. The results of the study: 1) the chain whisper game makes it easier for female students to memorize mufrhodat which is required by the madrasah as a condition for carrying out all exams, namely memorizing two thousand mufrhodat. 2) The positive impact of the chain whisper game: making it easier for students to memorize mufrhodat and improving their writing and writing skills, students do not feel bored and sleepy and are more enthusiastic in learning Arabic, increasing students' interest in learning Arabic. The negative effects of the serial whisper game: some students have difficulty hearing their friends' whispers because they are not clear, and some students find it difficult to write mufrhodat on the board.